Croatian Literature and the Problem of Periodization, 28.04.1987. Slavic Department, Cornell University - Gjurgjan, Ljiljana Ina (1987)
The lecture has addressed the topic of “irregular” periodization, claiming that the fact that some national literatures do not follow the model of European literary history does not make them inferior, but provides for their own autonomous dynamics of relating to the European tradition.